SOA with REST : principles, patterns & constraints for building enterprise solutions with REST - Erl, Thomas (Prentice Hall service-oriented computing series from Thomas Erl., 2012)
"This book illuminates the connection of the two domains--SOA and REST--in a manner that is concrete and practical, providing concise application to everyday architectural challenges. Fantastic!" -- Ryan Frazier, Technology Strategist, Microsoft "...a tour de force that elegantly applies REST principles to the industry-standard SOA framework described in prior titles in this series.... This book is a must-read for anyone developing REST services." -- Dave Slotnick, Enterprise Architect, Rackspace Hosting "This book undoubtedly will help SOA to reap the benefits from the main value propositions of Web architecture..." -- Dr. Erik Wilde, Architect, EMC Corporation "REST is so much more than just another type of interface implementation -- SOA with REST shows how the ecosystem of service compositions changes as new opportunities arise for service composition architecture designs. A comprehensive guide and a must-read for any serious IT architect considering REST-style services for application architectures." -- Roger Stoffers, Solution Architect, Hewlett Packard "Service-orientation and REST both are architectural styles that are cornerstones of modern applications and cloud computing. Both aim to deliver scalable, interoperable solutions, but their different roots don't always make them a natural fit. SOA with REST explains how the two styles can work together in enterprise environments. It discusses a design process for a services portfolio that meets the goals of SOA and at the same time designs services that comply with the established REST constraints. It also shows pragmatic approaches to meet enterprise-grade requirements with the REST programming style but relaxes constraints where necessary." -- Christoph Schittko, Director of Cloud Strategy, Microsoft "An excellent repertoire of service-oriented patterns that will prove handy when solving problems in the real world. The REST perspectives and principles will provide complete coverage of modern-day Web 2.0 style approaches. Highly recommended." -- Sid Sanyal , IT Architect, Zurich Financial Services.